(untitled) (Olhar de Professor, 2022)
In a society in constant transformation and rapid technological advances, the main characteristic of a competitive professional is the ability to create and apply science and technology in the generation of belongings and services. For this, good questions are cool, doubts that will highlight you as a professional and make a difference to the community as a whole. Thus, considering the need for progress and as contemporary changes in an increasingly globalized and hyperconnected world, the objective is to analyze the current learning scenario and the forms of teaching used as a subsidy for the development of the engineering student. To do so, it starts from the analysis of some historical and philosophical factors that led the student to a stiffening of his questioning power, to proceed with the analysis of active teaching methodologies, such as Problem Based Learning (ABL), Questioning Methodology (MP) and Team-Based Learning (ABE). The use of these tools allows the framing of the student as a manager of his own learning and leads to the granting of the need to search for alternative methods to break the passivity of the discente group.